Clima laboral en el gobierno autónomo descentralizado municipal Puebloviejo, Provincia de Los Ríos - Lucio Macias, Johanna Mercedes (2019)
The work environment is considered as a fundamental factor for the proper functioning of organizations, because it is the environment where daily work takes place, it influences factors such as work performance, satisfaction, motivation and productivity, such factors can be affected if there is no appropriate work environment, for an organization to progress, it is vital to generate a good work environment, so that the work environment is calm, safe, pleasant and stimulating for all, allowing to obtain results that favor the institution. The proposed case study aims to investigate the problems that affect the different activities carried out in the Municipal GAD of the San Francisco Canton of Puebloviejo